Condition monitoring based on IoT for predictive maintenance of CNC machines - Yahya Mohammed, Al-Naggar; Norlida, Jamil; Mohd Firdaus, Hassan; Ahmad Razlan, Yusoff (Elsevier B.V., 2021)
Machining operation must be maintained for a long time in every period to achieve high productivity and prevent sudden failure or breakdown. This study aims to monitor conditions of four CNC machines from different places simultaneously using Internet of things (IoT) for predictive maintenance. Vibration signals of four CNC machines are measured using an accelerometer to collect and send signals directly to the database in real time. Results showed that acceleration signal in both time and frequency domains can identify conditions of each machine in real time and simultaneously monitor the condition of four CNC machines at different places through IoT for predictive maintenance.